2015
DOI: 10.1021/acs.langmuir.5b03405
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Assembly of Polymer-Grafted Nanoparticles at Oil–Water Interfaces

Abstract: Using dissipative particle dynamics (DPD), I model the interfacial adsorption and self-assembly of polymer-grafted nanoparticles at a planar oil-water interface. The amphiphilic core-shell nanoparticles irreversibly adsorb to the interface and create a monolayer covering the interface. The polymer chains of the adsorbed nanoparticles are significantly deformed by surface tension to conform to the interface. I quantitatively characterize the properties of the particle-laden interface and the structure of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 69 publications
4
57
0
Order By: Relevance
“…This can be demonstrated by a high linear correlation coefficient R 2 =0.9908. This also proved that the sorption of oil on the grafted fibers was monolayer sorption [53,54]. From the obtained equation (Figure 10), we can identify the maximum oil sorption capacity is Q max =1/0.048=20.833 (g/g).…”
Section: Determination Of the Maximum Absorption Capacitysupporting
confidence: 53%
“…This can be demonstrated by a high linear correlation coefficient R 2 =0.9908. This also proved that the sorption of oil on the grafted fibers was monolayer sorption [53,54]. From the obtained equation (Figure 10), we can identify the maximum oil sorption capacity is Q max =1/0.048=20.833 (g/g).…”
Section: Determination Of the Maximum Absorption Capacitysupporting
confidence: 53%
“…Molecular simulations predict that the conformation of ligands grafted onto the NP surface can change upon adsorption to the interface due to the asymmetric environment surrounding the particles . Yong characterized the adsorption process, i.e., approaching and breaching of the interface, and subsequent change in conformation, of polymer‐grafted NPs via molecular simulation . They observed that grafted chains can undergo significant reconfiguration during adsorption by spreading onto the interface to maximize the reduction in surface tension (Figure a–f), indirect evidence for which has also been seen experimentally .…”
Section: Assembly Dynamics and In Situ Characterization Of Nanomatementioning
confidence: 70%
“…a–f) Snapshots of adsorption simulation of a single NP grafted with hydrophilic polymer chains. Reproduced with permission . Copyright 2015, American Chemical Society.…”
Section: Assembly Dynamics and In Situ Characterization Of Nanomatementioning
confidence: 99%
“…Meanwhile, experimental results by Wasan and Nikolov [26] showed that the nanoparticles could form two-dimensional (2-D) layered structures in the confines of the three-phase (solid-oil-aqueous phase) contact region and produce disjoining pressure that leads to the wettability alteration of the solid phase. Therefore, it has been believed that nanoparticles can change the interfacial tension, viscosity and wettability of fluids, which are important to many applications ranging from electronics cooling to oil recovery [30][31][32][33][34]. However, due to the additional particle-particle, particle-capillary and particle-fluid interactions [32,35], the presence of nanoparticles leads to a much more complicated imbibition process compared with pure fluids.…”
Section: Introductionmentioning
confidence: 99%